Dielectric energy storage material and preparation method and application thereof

By grafting polyetherimide in polypropylene and combining with polypropylene to form a dielectric energy storage material with high dielectric constant and breakdown field strength, the problems of low dielectric constant and low breakdown field strength of existing materials are solved, and the energy storage density and reliability are improved.

CN119661936AActive Publication Date: 2025-03-21GUANGDONG POWER GRID CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411796604.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing polypropylene dielectric energy storage materials have low dielectric constant and small breakdown field strength, resulting in low energy storage density and low reliability.

Method used

By chemically reacting polyetherimide with polypropylene grafted maleic anhydride, polypropylene grafted polyetherimide is formed and combined with polypropylene to form a dielectric energy storage material with high dielectric constant and breakdown field strength.

Benefits of technology

The dielectric constant and breakdown field strength of the material are significantly improved, and the energy storage density and energy storage efficiency of polypropylene-based dielectric energy storage film capacitors are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661936A_ABST
    Figure CN119661936A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of organic polymer dielectric materials, and particularly discloses a dielectric energy storage material and a preparation method and application thereof. The dielectric energy storage material disclosed by the invention is prepared from the following components in parts by weight: 5 to 35 parts of polypropylene grafted polyetherimide and 70 to 90 parts of polypropylene. According to the invention, the polypropylene grafted polyetherimide is added on the polypropylene matrix, and the polypropylene grafted polyetherimide can obviously improve the dielectric constant and the breakdown field strength of the material, thereby providing technical support for improving the energy storage density and the reliability of the capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer dielectric materials, and in particular relates to a dielectric energy storage material and a preparation method and application thereof. Background Art

[0002] Polypropylene (PP) film has high electrical strength, excellent self-healing properties, and low loss, and is widely used in capacitors. However, the current polypropylene film has a low dielectric constant and a small breakdown field strength, resulting in dielectric film capacitors still facing problems such as low energy storage density and low reliability. In the prior art, in order to increase the dielectric properties of PP, physical means can be used to disperse fillers with dielectric properties in the PP matrix to form polypropylene nanocomposite dielectric materials. However, in this physical mixing method, dielectric fillers generally need to be nanoscale, and nanoscale fillers are very easy to agglomerate, and the interface compatibility between nanofillers and PP matrix is ​​not good, which easily leads to internal inhomogeneity of the material system and decreased mechanical properties; at the same time, to ensure that the nanofillers are evenly dispersed in the PP matrix as much as possible, complex preparation processes and processing methods are required, which further increases production costs and limits the large-scale production and use of such polypropylene nanocomposite dielectric materials in the market. How to prepare a polypropylene material with high dielectric energy storage properties is a problem of great practical significance and urgent need to be solved. Summary of the invention

[0003] In view of the problems of low dielectric constant and low breakdown field strength of polypropylene dielectric energy storage materials involved in the above-mentioned prior art, the present invention will provide a dielectric energy storage material and a preparation method and application thereof.

[0004] To achieve the above purpose, the following technical solutions are specifically included:

[0005] In one aspect, the present invention provides a dielectric energy storage material, comprising the following components in parts by weight: 5-35 parts of polypropylene grafted polyetherimide and 70-90 parts of polypropylene.

[0006] Polyetherimide (PEI) has excellent high temperature resistance and dielectric properties. The present invention grafts it onto polypropylene (PP) by chemical means, introduces functional side chains into the PP main chain, forms polypropylene grafted polyetherimide (PP-g-PEI), and then compounding PP-g-PEI and PP to form a dielectric energy storage material, which can not only significantly improve the dielectric constant and breakdown field strength of the material, but also improve the polarity and interface compatibility of PP, improve the uniformity of the system, avoid the defect of poor compatibility of conventional fillers and PP physical blending methods, and further improve the energy storage density and energy storage efficiency of polypropylene dielectric energy storage film capacitors.

[0007] The type of polypropylene of the present invention is not particularly limited, and conventional dielectric polypropylene can achieve the purpose of the present invention. Preferably, the polypropylene has a melt mass flow rate of 0.5-20 g / 10 min, more preferably 1-5 g / 10 min, at 230° C. and 2.16 kg according to ISO1133.

[0008] Preferably, in the dielectric energy storage material, the mass percentage of the polypropylene grafted polyetherimide is 10-30%.

[0009] Further preferably, in the dielectric energy storage material, the mass percentage of the polypropylene grafted polyetherimide is 10-20%.

[0010] Within a certain range, as the content of PP-g-PEI in the dielectric energy storage material increases, the dielectric constant gradually increases and the breakdown field strength gradually decreases. At the above-mentioned mass percentage of polypropylene grafted polyetherimide, the dielectric energy storage material can simultaneously maintain a relatively high dielectric constant and breakdown field strength, laying the foundation for further improving the energy storage density and energy storage efficiency of polypropylene dielectric energy storage film capacitors.

[0011] In another aspect, the present invention provides a method for preparing the dielectric energy storage material, comprising the following steps:

[0012] (1) in the presence of a solvent, m-phenylenediamine and 4,4'-(4,4'-isopropyldiphenyloxy) diphthalic anhydride react to obtain a polyetherimide;

[0013] (2) in the presence of an interface agent, the polyetherimide and PP-g-MAH react to obtain polypropylene grafted polyetherimide;

[0014] (3) The polypropylene and the polypropylene grafted polyetherimide are mixed, melted, hot pressed and cooled to obtain the dielectric energy storage material.

[0015] In the preparation method of the present invention, based on polypropylene grafted maleic anhydride (PP-g-MAH), PP grafted PEI (PP-g-PEI) is prepared by a solid phase method, and the chemical structure of the PP-g-PEI is as follows:

[0016]

[0017] Here, m and n are the degree of polymerization.

[0018] Preferably, in step (1), the mass ratio of m-phenylenediamine to 4,4'-(4,4'-isopropyldiphenyloxy)diphthalic anhydride is (10-30):(50-80).

[0019] Preferably, in step (1), the solvent comprises dimethylacetamide (DMAC), the reaction time is 24-48 hours, and the reaction is carried out under stirring conditions and under the protection of an inert gas.

[0020] Preferably, in step (1), the concentration of m-phenylenediamine in the solvent is 10-20 wt.%.

[0021] Preferably, in step (2), the mass ratio of the polyetherimide to PP-g-MAH is (20-40):(5-20).

[0022] Preferably, in step (2), the solvent includes xylene, the reaction time is 2-5 hours, the reaction temperature is 80-100° C., and the reaction is carried out under stirring conditions and under the protection of an inert gas.

[0023] Preferably, in step (2), the mass ratio of the interfacial agent, polyetherimide and PP-g-MAH is interfacial agent:polyetherimide:PP-g-MAH=(200-300):(10-30):(20-40).

[0024] Preferably, in step (2), the mass percentage of MAH in the PP-g-MAH is 1-11%, more preferably 4-10%.

[0025] Preferably, in step (2), the PP-g-MAH has a melt mass flow rate of 0.5-10 g / 10 min when tested at 230° C. and 2.16 kg according to ISO1133.

[0026] Preferably, in step (3), the melting temperature is 190-220°C, and the melting time is 5-10 min.

[0027] Preferably, in step (3), the hot pressing pressure is 5-20 kPa, and the hot pressing time is 5-40 min.

[0028] In addition, the present invention also provides an application of the dielectric energy storage material in preparing a capacitor.

[0029] Preferably, the dielectric energy storage material has a frequency range of 0.1 Hz to 10 6 The dielectric constant is 2.35-2.6 at Hz.

[0030] Preferably, the dielectric energy storage material has a breakdown field strength of 200-450 kV / mm at 25° C., more preferably 300-400 kV / mm.

[0031] The dielectric energy storage material of the present invention has a relatively high dielectric constant and breakdown field strength. Using it as a material for preparing a capacitor can further improve the dielectric energy storage characteristics of the capacitor, such as further improving the energy storage density and reliability of the capacitor.

[0032] Compared with the prior art, the present invention has the following beneficial effects: the present invention adds polypropylene grafted polyetherimide to the polypropylene matrix, and the polypropylene grafted polyetherimide can significantly improve the dielectric constant and breakdown field strength of the material, providing technical support for improving the energy storage density and reliability of the capacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The figure is a flow chart for synthesizing polypropylene grafted polyimide (PP-g-PEI), wherein m and n involved in the chemical structural formulas of PEI, PP-g-MAH and PP-g-PEI are their respective degrees of polymerization.

[0034] Figure 2 Spectra of the dielectric energy storage materials of Examples 1-3 and Comparative Examples 1-2.

[0035] Figure 3 It is a graph showing the DC breakdown test results of the dielectric energy storage materials of Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0036] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0037] Polypropylene: Borealis, HC-300BF, melt mass flow rate of 3.3 g / 10 min as measured at 230° C. and 2.16 kg according to ISO 1133.

[0038] PP-g-MAH: SK General Chemical of South Korea, brand number 18722, melt mass flow rate tested at 230°C and 2.16 kg according to ISO1133 was 7.0 g / 10 min.

[0039] Example 1

[0040] A method for preparing a dielectric energy storage material comprises the following steps:

[0041] (1) In the presence of DMAC solvent, 15 parts by weight of m-phenylenediamine (the concentration of m-phenylenediamine in the solvent is 15 wt.%) and 65 parts by weight of 4,4'-(4,4'-isopropyldiphenyloxy)diphthalic anhydride are added, nitrogen is introduced to remove air from the system, and the reaction is carried out for 28 hours under nitrogen protection and stirring to obtain polyetherimide;

[0042] (2) 30 parts by weight of polyetherimide and 250 parts by weight of xylene as an interface agent were added to 15 parts by weight of PP-g-MAH, and nitrogen was introduced; then the mixture was placed in a 90°C heat-collecting constant temperature heating magnetic stirrer for 3 hours of oil bath reaction. After the oil bath reaction, the graft copolymer was filtered and rinsed with methanol to remove excess interface agent and DMAC solvent. The rinsed graft copolymer was placed in a 60°C vacuum drying oven for 1 hour to remove excess methanol. Finally, polypropylene grafted polyetherimide was obtained, and the synthetic route thereof is as shown in the attached figure. Figure 1 As shown;

[0043] (3) 90 wt.% polypropylene and 10 wt.% polypropylene grafted polyetherimide are mixed in a blender at a blending temperature of 190-200°C, a blending speed of 5-15 rpm, and a blending time of 10-30 min; then transferred to a twin-screw extruder, melted at 200°C for 5 min, and finally, hot-pressed in a flat vulcanizer at pressures of 5 kPa, 10 kPa, 15 kPa, and 20 kPa for 5 to 10 minutes, followed by water cooling for 6 to 10 minutes (the device is water-cooled), and cold-pressed to room temperature to obtain a dielectric energy storage material film sample with a thickness of 80-100 μm.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that in step (3), this embodiment uses 80 wt.% polypropylene and 20 wt.% polypropylene grafted polyetherimide to mix in a blender, and the rest is the same.

[0046] Example 3

[0047] The difference between this embodiment and embodiment 1 is that in step (3), this embodiment uses 70 wt.% polypropylene and 30 wt.% polypropylene grafted polyetherimide to mix in a blender, and the rest is the same.

[0048] Comparative Example 1

[0049] This comparative example uses pure polypropylene raw material, commercially available product Borealis HC-300BF, which is melted at 180-200°C for 5 minutes, then hot-pressed for a certain period of time under stepped pressure on a flat vulcanizer, and cold-pressed to room temperature to obtain the desired film.

[0050] Comparative Example 2

[0051] In this comparative example, 90wt.% polypropylene and 10wt.% PP-g-MAH are mixed in a blender at a blending temperature of 190-200°C, a blending speed of 5-15rpm, and a blending time of 10-30min; then the mixture is transferred to a twin-screw extruder, melted at 180-200°C for 5min, and finally, hot-pressed under stepped pressure on a flat vulcanizer for a certain period of time, and cold-pressed to room temperature to obtain a dielectric energy storage material film sample.

[0052] Performance Test:

[0053] (1) Circular gold electrodes with diameters of 22 mm and 25 mm were sputtered on the upper and lower surfaces of the films obtained in the above-mentioned embodiment and comparative example respectively by an ion sputtering instrument, and then the spectrum thereof at room temperature was tested by a broadband dielectric impedance meter. The results are as follows: Figure 2 shown.

[0054] (2) The films prepared in the above-mentioned embodiments and comparative examples were placed in a withstand voltage tester for DC breakdown test. The two breakdown electrodes used in the test were both spherical copper electrodes with a diameter of 25 mm, and the voltage rise rate of the test was 1 kV / s. Each sample film was measured 10 times to ensure the comparability of the results, and the breakdown results were analyzed by Weibull function. The results are shown in Figure 2. Figure 3 shown.

[0055] Depend on Figure 2 It can be seen that the dielectric energy storage film materials in Examples 1-3 of the present invention have a high 6 Hz, the dielectric constant is 2.35-2.6. At a frequency of 100Hz, the dielectric constant of the film of comparative example 1 is 2.28, the dielectric constant of the film of comparative example 2 is 2.41, and the dielectric constants of the films of embodiments 1-3 are 2.46, 2.49, and 2.51, respectively. Compared with pure PP and the composite system of PP-g-MAH and PP, the dielectric energy storage material obtained by compounding PP and PP-g-PEI of the present invention has a significantly improved dielectric constant; at the same time, as the content of PP-g-PEI added to the system increases, the dielectric constant of the obtained dielectric energy storage material continues to rise.

[0056] Depend on Figure 3It can be seen that at 25°C, the characteristic breakdown field strength of Example 1 is 398.53 kV / mm, and the characteristic breakdown field strength of Comparative Example 1 is 334.88 kV / mm. Compared with Comparative Example 1, the breakdown field strength of the film of Example 1 is increased by 19.0%. It can be seen that the dielectric energy storage material obtained by compounding PP and PP-g-PEI of the present invention has a significantly improved breakdown field strength than that of pure PP. It can be seen that in PP-g-PEI, the introduction of PEI can introduce deeper traps into the polypropylene matrix, and these deep traps can capture more carriers, thereby inhibiting the transfer of charges and improving the breakdown field strength of the material. In addition, the inventors of the present invention found that within a certain range, as the content of PP-g-PEI in the dielectric energy storage material increases, the thickness of the material's lamellae will be significantly reduced, that is, more imperfect thin lamellae will be formed, and these thin lamellae will cause an increase in structural defects in the internal crystallization region. These defects become electric field concentration points, causing electric field distortion and increasing the risk of electrical breakdown. Therefore, it is necessary to make a trade-off between the introduction of deep traps (increasing the breakdown field strength) and the crystallization ability of the material (the solution of the present invention is embodied in reducing the breakdown field strength) to achieve the ultimate purpose of increasing the breakdown field strength. Therefore, in the dielectric energy storage material of the present invention, the mass percentage of PP-g-PEI is preferably 10-20%.

[0057] The dielectric energy storage properties of a material are closely related to its breakdown field strength and dielectric constant. The dielectric energy storage material obtained by compounding PP and PP-g-PEI in the present invention has a higher dielectric constant and breakdown field strength than similar products, and has excellent dielectric energy storage properties.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A dielectric energy storage material, characterized in that: The invention comprises the following components in parts by weight: 5-35 parts of polypropylene grafted polyetherimide and 70-90 parts of polypropylene.

2. The dielectric energy storage material according to claim 1, characterized in that In the dielectric energy storage material, the mass percentage of the polypropylene grafted polyetherimide is 10-30%.

3. The dielectric energy storage material according to claim 1, characterized in that The melt mass flow rate of the polypropylene measured at 230° C. and 2.16 kg according to ISO 1133 is 0.5-20 g / 10 min.

4. A method for preparing the dielectric energy storage material according to any one of claims 1 to 3, characterized in that: The steps include: (1) in the presence of a solvent, m-phenylenediamine and 4,4'-(4,4'-isopropyldiphenyloxy) diphthalic anhydride react to obtain a polyetherimide; (2) in the presence of an interface agent, the polyetherimide and PP-g-MAH react to obtain polypropylene grafted polyetherimide; (3) The polypropylene and the polypropylene grafted polyetherimide are mixed, melted, hot pressed and cooled to obtain the dielectric energy storage material.

5. The method for preparing a dielectric energy storage material according to claim 4, characterized in that: In step (1), the mass ratio of m-phenylenediamine to 4,4'-(4,4'-isopropyldiphenyloxy)diphthalic anhydride is (10-30):(50-80).

6. The method for preparing a dielectric energy storage material according to claim 4, characterized in that: In step (1), the solvent includes dimethylacetamide, the reaction time is 24-48 hours, and the reaction is carried out under stirring conditions and under the protection of an inert gas.

7. The method for preparing a dielectric energy storage material according to claim 4, characterized in that: In step (2), the mass ratio of the polyetherimide to PP-g-MAH is (20-40):(5-20).

8. The method for preparing a dielectric energy storage material according to claim 4, characterized in that: In step (2), the solvent includes xylene, the reaction time is 2-5 hours, the reaction temperature is 80-100° C., and the reaction is carried out under stirring conditions and under the protection of an inert gas.

9. The method for preparing a dielectric energy storage material according to claim 4, characterized in that: In step (3), the melting temperature is 180-200°C.

10. Use of the dielectric energy storage material according to any one of claims 1 to 3 in preparing a capacitor.

Citation Information

Patent Citations

  • Preparation method of polyetherimide coated magnesium oxide / polypropylene nano composite film

    CN114369309A

  • High-energy-storage polyetherimide dielectric material as well as preparation method and application thereof

    CN118126322A

  • Preparation method and application of high-energy-storage polyetherimide-polymethyl methacrylate organic composite material

    CN119039614A

  • Polyether imide film for capacitor

    JP2008274023A

  • Polyetherimide Compatible Polymer Blends for Capacitor Films

    US20170084394A1